Desenvolvimento de micropartículas contendo suco de tomate via gelificação iônica - Rocha, Lenizy Cristina Reis (2017)
The tomato has high nutritional value besides being a fruit rich in vitamins and phenolic compounds, and possessing bioactive compounds, as the carotenoids. The most expressive carotenoid in tomatoes is lycopene, which is characterized within the class of antioxidants and thus presents several benefits to human health, such as cancer prevention. The chemical characteristics of carotenoids make them susceptible to oxidation in the presence of light and temperature. Thus, microencapsulation of tomato juice followed by drying results in more stable particles and more protection to the tomato compounds. The present work had as objective to develop alginate microparticles, containing tomato juice, through ionic gelation technique. In addition, maltodextrin and inulin were used as carrier materials in the microsphere formulation. The microparticles were further stabilized by freeze-drying and air circulating oven. In the first stage, through the development of the microspheres by ionic gelation, the contributions of the wall materials used to protect tomato bioactive compounds the microencapsulation process and storage at different temperatures were verified. In presence of maltodextrin and inulin, higher values of encapsulation efficiency were obtained. The stability of the carotenoid lycopene in presence of other polymers was superior in relation to the use of only alginate. Stability was influenced by storage temperatures, where higher coloring and lycopene degradation when temperature increased. In the development of the second stage, the stabilization of the microspheres by means of drying in an air circulation oven and freeze-drying together with maltodextrin as carrier material in different concentrations was carried out. It was verified that freeze-drying process was more efficient in the retention of the carotenoids. The addition of maltodextrin significantly influenced the characteristics of the materials. The freeze-dried microspheres presented higher retention of staining. In addition, lower moisture absorption levels were obtained in the presence of maltodextrin at all concentrations. Thus, the microencapsulation of tomato juice by ionic gelation, followed by drying, results in protection of its active compounds, such as lycopene. The development of microparticles containing tomato juice has potential for use in the formulation of innovative foods with functional characteristics.